2000
DOI: 10.1007/s002040050647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human plasma on the reactivation of sarin-inhibited human erythrocyte acetylcholinesterase

Abstract: The reactivation of organophosphate-inhibited acetylcholinesterase (AChE) by oximes inevitably results in the formation of highly reactive phosphoryloximes (POX), which are able to re-inhibit the enzyme. In this study, the dependence of POX formation on AChE concentration was investigated with sarin-inhibited human erythrocyte AChE (EryAChE). A marked dependence was found with obidoxime but not with the experimental oxime HI 6, suggesting great differences in the decomposition rates of the respective POXs. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…This holds true for previously published data obtained with sarin, soman, and tabun (Becker et al 1997). For practical administrations it might be useful to accelerate the third step of the direct reaction, i.e., the degradation of the POXs, by addition of bacterial (Ashani et al 1998;Leader et al 1999;HerkenhoV et al 2004) or human plasma enzymes Worek et al 2000).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…This holds true for previously published data obtained with sarin, soman, and tabun (Becker et al 1997). For practical administrations it might be useful to accelerate the third step of the direct reaction, i.e., the degradation of the POXs, by addition of bacterial (Ashani et al 1998;Leader et al 1999;HerkenhoV et al 2004) or human plasma enzymes Worek et al 2000).…”
Section: Resultssupporting
confidence: 70%
“…POXs were identiWed as highly toxic anticholinesterases, even 10-to 100-fold more toxic than their parent compounds (Hackley et al 1959;Lamb et al 1964Lamb et al , 1965Schoene 1973;Nenner 1974;de Jong and Ceulen 1978;Harvey et al 1984Harvey et al , 1986Worek et al 2000). The stability of the POX intermediate seems to be an important factor determining the velocity of the direct reaction.…”
Section: Discussionmentioning
confidence: 99%
“…HI 6 (Worek et al, 2000;Ashani et al, 2003;Leader et al, 1999;Hackley et al, 1959). Due to the reactivation reaction, the concentration of phosphonyloxime is correlated with the concentration of phosphylated AChE (Harvey et al, 1984;Worek et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…93 This enzyme, however, is apparently unable to inactivate phosphonyl oxime derivatives. 94 Mechanistic studies of oxime action have also shown that two binding sites are involved, i.e., cholinesterases have two binding sites for reversible ligands: (1) an acylation (catalytic) site at the base of the active site gorge and (2) a peripheral (allosteric) site at its mouth. 95 Reversible ligands, such as the oximes, may bind to cholinesterases either at the catalytic site or at the allosteric site, or at both sites of the enzymes, thus explaining the mechanism of protection afforded by oxime administration.…”
Section: Mechanism Of Action Of Pyridinium Oximesmentioning
confidence: 99%